Realization of the Concessive Semantic-syntactic Relationships in Complex Sentences (Case Study of I. Franko Scientific Works) (Linguostylistic Studies, 2019)
The article is devoted to the analysis of the peculiarities of the syntactical organization of the functional-semantic category of concession in a complex sentence with opposing-concessive and separation-concessive relationships in the I. Franko scientific texts. The study has revealed a significant delineation of concessive relations in the composite sentences with open and closed structures, the means of their grammatical realization are systematized and the peripheral zone of the functional-semantic category of concession is argued in the article. The purpose of the study is to identify the peculiarities of the syntactical organization of the functional-semantic category of concession in a composite sentence with opposing-concessive and separation-concessive relations in the I. Franko scientific texts. The research methodology involved several methods: the descriptive method made it possible to define and thoroughly investigate the construction of the clauses of concession, and to systematize and clarify their semantic-syntactic structure; systematic analysis was used to identify varieties of clauses of concession. At various stages of the study, the methods of component analysis were used to study the cases of extending and reducing basic or derivative concessive constructions, and transformational analysis - in the cases of various syntactic unit transformations. The syntactic features of I. Franko’s scientific texts are of great interest and require detailed scientific analysis. Analysis of the scientific papers in the field of syntax underpins the conclusion that there are only several investigations in the Ukrainian linguistics which highlight the issue of the syntaxemes with concession relationships, functioning in I. Franko's scientific texts.
Keywords: open and closed structures; concession; concessive semantic-syntactic relations; adversarial-concessive relations; separation-concessivee relations; functional-semantic concessive category